Seasonal social dilemmas - Lucas S. Flores; Amanda de Azevedo-Lopes; Chadi M. Saad-Roy; Arne Traulsen (npj Complexity)
Abstract Social dilemmas, where the collective interest is at odds with those of individuals, were widely discussed in the context of mitigating the spread of COVID-19. Non-pharmaceutical interventions (NPIs) such as reducing personal contact or wearing masks to protect others were often viewed as static social dilemmas. In the context of respiratory diseases, which predominantly spread during winter, these dilemmas can reoccur seasonally. We extend a game-theoretic model for individual NPI adherence coupled to an epidemiological model by introducing a seasonal transmission rate. Adherence to an NPI may be a transient social dilemma, depending on season and the associated infections in the population. Decisions to follow NPIs in a seasonal context can change infection peaks in the population. Our work highlights a complex interdependence between behavior and seasonal disease, which has implications for epidemiology, but also for the field of social dilemmas, which have been mostly viewed as static so far.